Republic of Lithuania : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Selected Issues paper examines the reasons behind Lithuania's low tax-GDP ratio relative to the European Union (EU). At end-2015, Lithuania had nearly the lowest tax-GDP ratio in the EU, along with Bulgaria and Romania. The tax revenue shortfall relative to the EU is for the most part attributable to weak tax administration and tax policy, with the structure of the economy playing a secondary role. The second largest contribution to the tax revenue shortfall relative to the EU comes from social security contributions. The shortfall is driven primarily by the structure of the economy, and to a smaller extent by tax administration.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet